Pengembangan Sistem Rekomendasi Rute Gowes di Kota Malang berbasis Android - Ahmad Aulia Fahmi; Ratih Kartika Dewi; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Cycling has become one of the few favorite sports activities for many city dwellers in Indonesia. Cycling is the activity of pedaling on a bicycle with a certain rhythm. One of the cities with a significant amount of cyclists is Malang City, located in the province of East Java. However, for certain individuals, such as youngsters, have had difficulty finding cycling routes in Malang city. An application that recommends cycling routes is capable of providing cycling routes based on a user's preference.The cycling route recommendation application in Malang city is designed using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method which used criteria such as the distance of a cycling route, traveling time of the route, and difficulty of the terrain and implemented on an Android operating system. The application underwent three testing methods which were blackbox testing, algorithm validation testing and usability testing. Blackbox testing is the process of observing if the system output is the same as the intended output. The results from the blackbox method resulted in a 100% score, which is the equivalent of all functionalities fulfilling expectations. Testing the algorithm validation from testing is intended to compare the results of the system output with manual calculations. Testing the algorithm validation in this study produces a value of 100% or the system output is the same as manual calculation. Whereas the usability is tested thru the system's interface which was tested by users. The usability testing method resulted in a score of 84,5 from a predetermined scale (have grade B) and is equivalent to stating that the system was given a high score by the users.